2019
DOI: 10.1038/s41598-019-40670-y
|View full text |Cite
|
Sign up to set email alerts
|

Fine particulate matter (PM2.5) inhibits ciliogenesis by increasing SPRR3 expression via c-Jun activation in RPE cells and skin keratinocytes

Abstract: Exposure to fine particulate matter (PM) with diameter <2.5 µm (PM2.5) causes epithelium injury and endothelial dysfunction. Primary cilia are sensory organelles that transmit extracellular signals into intracellular biochemical responses and have roles in physiology. To date, there have been no studies investigating whether PM2.5 affects primary cilia in skin. We addressed this in the present study using normal human epidermal keratinocytes (NHEKs) and retinal pigment epithelium (RPE) cells. We found that for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
(50 reference statements)
2
20
0
Order By: Relevance
“…SPRR3 was shown to be upregulated in keratinocytes treated with PM 2.5 [132]. SPRR3 upregulation has been shown to decrease ciliogenesis in vitro [140], which is responsible for suppressing skin pigmentation in melanocytes [151].…”
Section: Physical Barriermentioning
confidence: 97%
See 1 more Smart Citation
“…SPRR3 was shown to be upregulated in keratinocytes treated with PM 2.5 [132]. SPRR3 upregulation has been shown to decrease ciliogenesis in vitro [140], which is responsible for suppressing skin pigmentation in melanocytes [151].…”
Section: Physical Barriermentioning
confidence: 97%
“…Additionally, markers for proliferation, such as Ki67, 5-bromo-2′-deoxyuridine (BrdU) incorporation, and proliferating cell nuclear antigen (PCNA), were shown to be decreased upon PM exposure [125,130]. Reduced expression of differentiation and proliferation markers was also shown in 2D models, i.e., HaCaT and NHEK cells [122,125,127,140,141,143,144].…”
Section: Physical Barriermentioning
confidence: 98%
“…Skin is the largest organ of the human body, as well as the primary organ which is exposed to outdoor contaminants. Exposure to PM causes epithelium damage, and endothelial dysfunction has been reported previously [8,9,38]. PM induce skin damages or diseases mainly through stimulating inflammatory response and oxidative stress [5,39].…”
Section: Discussionmentioning
confidence: 78%
“…However, the mechanisms of how PM induces and aggravates eczema in humans have not yet been elucidated. It is likely that PM induces the disruption of the epidermis by modulating the structural proteins including small proline-rich (SPRR) family, occludens-1 (ZO-1), keratins, laggrin, and claudin-1 [39][40][41][42][43][44][45] , thereby resulting in both increased epithelial and endothelial barrier permeability 46 .Moreover, a previous study reported that the penetration of PM was observed in both intact and barrier-disrupted skin in vivo, resulting in in ammatory responses 47 . Current scienti c opinions on the down-stream mechanisms through which air pollutants affect skin health mainly include: 1) elevation of oxidative stress via exogenous and endogenous reactive oxygen species (ROS) generation, which is a series of a highly reactive chemical substances.…”
Section: Discussionmentioning
confidence: 99%